Generic Health-Related Quality of Life after Repair of Esophageal Atresia and Its Determinants within a German–Swedish Cohort - Flieder, Sofie; Dellenmark-Blom, Michaela; Witt, Stefanie; Dingemann, Carmen; Quitmann, Julia H.; Jönsson, Linus; Gatzinsky, Vladimir; Chaplin, John E.; Dammeier, Barbara Gómez; Bullinger, Monika; Ure, Benno M.; Abrahamsson, Kate; Dingemann, Jens (European Journal of Pediatric Surgery, 2019)
Aim Despite advances of outcomes of esophageal atresia (EA), knowledge on patients' health-related quality of life (HRQoL) is sparse. Due to the heterogeneity of EA, larger cohorts need to be investigated to ensure reliability of data. Aim was to determine generic HRQoL after EA repair in a Swedish–German cohort.Patients and Methods Ethical approval was obtained. A total of 192 patients (2–18 years; 134 Swedish; 58 German) were included. Clinical data were reviewed. EA was classified in “severe” and “mild/moderate.” Pediatric Quality of Life Inventory 4.0 Generic Core Scale (PedsQL 4.0) was used in appropriate versions (2–7 years; 8–18 years; self- [SR] and proxy report [PR]) to determine generic HRQoL.Results Swedish and German samples were clinically and demographically comparable. HRQoL was lower in “severe EA” versus “mild/moderate” (2–18 years; total score; PR 85.6 vs. 73.6; p < 0.001) and Gross A versus Gross C type EA (2–7 years; total score; PR 61.0 vs. 79.3; p = 0.035). Total HRQoL was higher in the Swedish versus German sample (2–18 years; total score; PR 82.3 vs. 72.7; p = 0.002). HRQoL was impaired in the German sample versus healthy population (2–18 years; total score; PR 72.7 vs. 82.7; p = 0.001). In German patients (8–18 years), HRQoL was higher in SR versus PR (80.7 vs. 74.7; p = 0.044). Patients' age and presence of VACTERL association or isolated anorectal malformations did not affect HRQoL. Various differences were detected regarding different dimensions of PedsQL 4.0.Conclusion In this first international study, we found several differences in perception of generic HRQoL. HRQoL appears to be determined by the type of EA and severity rather than patients' age or the presence of typical associated malformations. Country-specific differences may be culturally dependent, but further investigations are suggested. A condition-specific instrument validated for EA may provide additional insights.
Keywords: esophageal atresia; long-term follow-up; outcome; health-related quality of life